Experience with 102 Frameless Stereotactic Biopsies Using the neuromate Robotic Device - Yasid, Hamzah; Hoff, Hans-Joachim; Blümcke, Ingmar; Simon, Matthias (World Neurosurgery, 2019)
OBJECTIVE: Stereotactic biopsy is a standard procedure in neurosurgery. In addition to or even replacing frame-based stereotaxy, some centers also use frameless imaging-based techniques and more recently robotic systems. Here we report a retrospective analysis of our experience with 102 consecutive biopsies performed in our institution using the neuromate robotic device.
CRIS-Team WoS Importer:2019-04-18